2016
DOI: 10.1111/acem.12939
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Resource Intensity and Cost Among High Users of the Emergency Department

Abstract: Objectives: High users of emergency department (ED) services are often identified by number of visits per year, with little exploration of the distribution/pattern of visits over time. The purpose of this study was to examine patient-and encounter-level factors and costs related to periods of short-term resource intensity among high users of the ED within a tertiary care teaching facility. Methods:We identified all adults with at least three visits to the Ottawa Hospital ED within a 1-year period from April 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…SHarED participants’ locally determined criteria for identifying HIUs mirrored the lack of a single definition of HIUs in the literature,25–27 as local differences in population characteristics and services influence the heterogeneity of this diverse group of individuals with complex health needs 2 6 12 24–26 28 29…”
Section: Discussionmentioning
confidence: 99%
“…SHarED participants’ locally determined criteria for identifying HIUs mirrored the lack of a single definition of HIUs in the literature,25–27 as local differences in population characteristics and services influence the heterogeneity of this diverse group of individuals with complex health needs 2 6 12 24–26 28 29…”
Section: Discussionmentioning
confidence: 99%
“…All studies examined pain, in differing significance, with the vast majority examining reported chronic pain. Specific examinations of pain in the various studies included pelvic pain reported from indigent women in (43), oral pain (52), headache or migraine pain (54,49), and finally, inflammatory diseases, associated with pain, such as arthritis (54)(55)(56)(57). used to classify participants according to their overall pain severity.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Moreover, frequent ED attendance can be viewed as characteristic of a complex system [22], which requires solutions at a system level as well as at the individual level [22,23], thus, a system-wide approach has been recommended [13,24]. SHarED participants' locally determined criteria for identifying HIUs mirrored the lack of a single definition of HIUs in the literature [25][26][27], as local differences in population characteristics and services influence the heterogeneity of this diverse group of individuals with complex health needs [2,3,12,[24][25][26]28,29].…”
Section: Ed Staff Surveymentioning
confidence: 99%